Synthesis, Superstructure, and Vacancy‐Ordering in 2H‐CuxTa1+ySe2 (x, y = 0.52, 0 and 0.16, 0.08)12. Issue 2 (13th November 2014) - Ali, Sk Imran; Mondal, Swastik; van Smaalen, Sander
Abstract Single crystals of CuxTa1+ySe2 were grown by chemical vapor transport. Single crystals of different compositions were obtained at slightly different reaction conditions from mixtures of the reactants of the same nominal composition. It is suggested that different diameters of the ampoules imply different contributions of convection and diffusion to the mass transport, and thus are responsible for different ratios of the amount of Cu, Ta, and Se transported. 2H‐Cu0.52TaSe2 (x = 0.52, y = 0) is formed in the narrower ampoule (diameter 15 mm). The crystal structure is based on the MoS2 type of stacking of TaSe2 layers. Partial ordering of Cu over the tetrahedral sites is responsible for a 2a0 × 2b0 × c0 superstructure with hexagonal P<alternatives> <![CDATA[6]]> <inline-graphic xlink:href="ark:/27927/pgh3xswfdrc" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>m2 symmetry [a0 = 3.468 (1) Å, c0 = 13.568 (3) Å]. 2H‐Cu0.16Ta1.08Se2 (x = 0.16, y = 0.08) is formed in the wider ampoule (diameter 18 mm). It possesses a NbS2‐type of stacking. A superstructure is not formed, but the presence of Cu and intercalated Ta in alternating van der Waals gaps is responsible for the reduction of symmetry from P63/mmc to P<alternatives> <![CDATA[6]]> <inline-graphic xlink:href="ark:/27927/pgh3xswff5h" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>m1 [a0 = 3.439 (2) Å, c0 = 12.870 (2) Å]. Single crystals are formed towards the hotter side of the ampoules up to a temperature of 1168 K in both reactions.